PAI Interdisipliner di Sekolah: Membangun Model Pembelajaran yang Intergratif dan Holistik di Era Digital - Tu’aini Tu’aini; Ishomuddin Ishomuddin; Abdul Haris (Departement of Mathematics Education, 2024)
In the current era, the learning process needs to be carried out in an integrative manner, especially as technology has developed to such an extent. The learning process is not only carried out technologically, but also contains intellectual, moral and skill elements. This article aims to discuss how the PAI learning process is carried out in an integrated and holistic manner. This study uses descriptive qualitative research in the form of library research. Excavating library data focused on several concepts regarding interdisciplinary approaches, PAI learning, and similar relevant concepts. Data analysis uses a content analysis model. This study found that interdisciplinary PAI learning is part of integrated learning. Interdisciplinary learning will essentially provide students with a holistic learning experience, because there is general subject matter content included in the learning. PAI material can be integrated with several subjects, such as science, social studies, civics and information technology. Integrated learning is realized in integrative thematic learning which combines competencies from several subjects as representatives of scientific disciplines into a network of certain themes. Its relevance is increasingly evident because the newest curriculum, the independent curriculum, does not eliminate it but instead enriches it with an open attitude to other relevant approaches.